New specific synonymies and taxonomic notes on Neotropical blackflies (Diptera: Simuliidae) - Hernández, L. M.; Shelley, A. J. (Zootaxa, 2005)
In this paper we clarify the status of some poorly known blackfly species from the Neotropical Region. Information is provided about their depositories, their condition, and already-established synonyms. Fifteen new synonyms are established, two species are assigned to a different subgenus, and five lectotypes are designated based on an examination of type material. The following new synonyms are proposed: Simulium tarsatum Macquart (= S. mexicanum Bellardi, S. seriatum Knab, S. aureopunctatum Malloch, S. placidum Knab, S. lugubre Lutz & Nuñez Továr, S. turgidum Hoffmann, Trichodagmia laticalx Enderlein, T. latidigitus Enderlein, S. bellardii Py-Daniel & Moreira Sampaio); S. nigrimanum Macquart (= T. spadicidorsum Enderlein); and S. townsendi Malloch (= S. chalcocoma Knab, T. ecuadoriensis Enderlein, T. latitarsis Enderlein, T. strigata Enderlein, S. muiscorum Bueno, Moncada & Muñoz de Hoyos). Five lectotypes are designated for the following species names: T. laticalx, T. latidigitus, T. spadicidorsum, T. ecuadoriensis and T. latitarsis. Two species, S. tarsale Williston & S. tarsatum Macquart, previously unplaced in the genus Simulium s.l. are now assigned to the subgenus Hemicnetha Enderlein.